2020
DOI: 10.1007/s42452-020-2172-y
|View full text |Cite
|
Sign up to set email alerts
|

Talc filled polylactic-acid biobased polymer composites: tensile, thermal and morphological properties

Abstract: Global warming due to human activities (i.e., burning fossil fuels) has led to many issues, such as extreme weather (storm or drought) and rise in sea level making low land uninhabitable. One of the solutions to mitigate the global warming is to promote the use of biobased material. In this work, various dosage of talc powder ranged from 5, 10, 30 and 40 wt% were added into polylactic acid (PLA) to form biobased polymer composites. The biobased polymer composite has the potential to replace fossil-based polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…However, the increase of thermal stability with the addition of organically modified clay in PHB started to reverse when the particle content was increased from 5 wt % to 10 wt % [ 53 ]. In a recent study of talc-reinforced PLA composites, although the composites with 5, 10, and 30 wt % talc showed slightly higher on-set degradation temperatures than PLA, the addition of 40 wt % talc decreased the on-set degradation temperature by 24 degrees [ 54 ]. Mechanical and morphological analysis in that study showed the agglomeration of the particles and the presence of voids in and around the particle clusters.…”
Section: Resultsmentioning
confidence: 99%
“…However, the increase of thermal stability with the addition of organically modified clay in PHB started to reverse when the particle content was increased from 5 wt % to 10 wt % [ 53 ]. In a recent study of talc-reinforced PLA composites, although the composites with 5, 10, and 30 wt % talc showed slightly higher on-set degradation temperatures than PLA, the addition of 40 wt % talc decreased the on-set degradation temperature by 24 degrees [ 54 ]. Mechanical and morphological analysis in that study showed the agglomeration of the particles and the presence of voids in and around the particle clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements were conducted with polymer granules (PLA1/0, PLA2/0), injection molded specimens (sample points with 1-5 wt% of talc), and masterbatches (PLA1/30, PLA2/30) expected due to the reported effect of talc, which weakens the permeability and therefore prevents the outdiffusion of the volatile compounds that evolve during decomposition. 21 The miscibility of the composites changed at 2-4 wt% talc loadings, which likely explains the dip observed in the TGA profile at 2-3 wt% talc loading.…”
Section: Thermal Characteristicsmentioning
confidence: 93%
“…Increased elastic modulus has been explained by the stress transfer from the polymer matrix to the talc particle. 21…”
Section: Tensile Strength and Elongationmentioning
confidence: 99%
See 2 more Smart Citations